2009
DOI: 10.1088/0957-4484/20/36/365601
|View full text |Cite
|
Sign up to set email alerts
|

Dye-sensitization of self-assembled titania nanotubes prepared by galvanostatic anodization of Ti sputtered on conductive glass

Abstract: Self-organized porous TiO(2) nanotubes (NTs) were prepared on conductive glass by galvanostatic anodizing of sputtered titanium in an NH(4)F /glycerol electrolyte. DC magnetron sputtering at an elevated substrate temperature (500 degrees C) was used to deposit 650 nm thick titanium films. After anodizing, NTs, 830 nm long, with an average external diameter of 92 nm, were grown; this gave a high conversion rate of oxide from titanium (1.9), with a 220 nm thick layer of titanium, which was not oxidized, located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 64 publications
2
37
2
Order By: Relevance
“…Furthermore, recombination resistant, R ct , was obtained 55.03 X that is comparable with literature data [26], implying that recombination of electrons through the electrolyte is not the dominant effect limiting photovoltaic performance.…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, recombination resistant, R ct , was obtained 55.03 X that is comparable with literature data [26], implying that recombination of electrons through the electrolyte is not the dominant effect limiting photovoltaic performance.…”
Section: Resultssupporting
confidence: 84%
“…Song et al [5] found that 90% of horseradish peroxidase was released in the first minute from untreated TiO 2 nanotubes and adding hydrophobic monolayer of octadecylphosphonic acid only improved the release rate by less than two orders. TNTs have been fabricated on a range of non-native substrates including silicon, glass, transparent conducting oxide (TCO)-coated glass, polyimide, and stainless steel [7][8][9][10][11][12][13] .Highly ordered titania nanotube (TNT) arrays on Ti surface fabricated by self-ordering electrochemical anodization have attracted increasing attention due to their excellent biocompatibility, high surface-to-volume ratio,…”
Section: Introductionmentioning
confidence: 99%
“…A few attempted to prepare TiO 2 nanotubes array directly on a transparent conductive substrate as a way to overcome the back-side illumination effects [3,[23][24]. The fabrication of this structured photoelectrode requires a deposition of metal titanium film on the conductive glass substrate in advance and causing the titanium film to undergo an anodization, resulting in the formation of nanotubes structure.…”
Section: Introductionmentioning
confidence: 99%